2013
DOI: 10.1152/ajprenal.00139.2013
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of CCL2/CCR2 in rat micturition reflexes and somatic sensitivity with urinary bladder inflammation

Abstract: Arms L, Girard BM, Malley SE, Vizzard MA. Expression and function of CCL2/CCR2 in rat micturition reflexes and somatic sensitivity with urinary bladder inflammation. Am J Physiol Regul Integr Comp Physiol 305: F111-F122, 2013. First published April 17, 2013 doi:10.1152/ajprenal.00139.2013.-Chemokines are proinflammatory mediators of the immune response, and there is growing evidence for chemokine/receptor signaling involvement in pronociception. Bladder pain syndrome (BPS)/interstitial cystitis (IC) is a chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 83 publications
5
65
0
Order By: Relevance
“…Previous studies reported that inflammatory cytokines can cause sensitization of polymodal C-fibers and facilitate Aβ input to the spinal cord leading to overactivity of the bladder [20, 21]. Arms reported that CCL2 expression was elevated in CYP-induced cystitis in rat and blockage of its high-affinity receptor was associated with increased bladder capacity and decreased void frequency [22]. In our study, antimuscarinics attenuated the CCL2, CCL5, and IL-6 expressions and the BOO with antimuscarinics groups had significantly longer micturition interval.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that inflammatory cytokines can cause sensitization of polymodal C-fibers and facilitate Aβ input to the spinal cord leading to overactivity of the bladder [20, 21]. Arms reported that CCL2 expression was elevated in CYP-induced cystitis in rat and blockage of its high-affinity receptor was associated with increased bladder capacity and decreased void frequency [22]. In our study, antimuscarinics attenuated the CCL2, CCL5, and IL-6 expressions and the BOO with antimuscarinics groups had significantly longer micturition interval.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder catheter implantation was performed in normal rats as previously described [7,9,13] . Briefly, rats were anesthetized by intraperitoneal injection of pentobarbital sodium (50 mg/kg).…”
Section: Intravesical Catheter Implantationmentioning
confidence: 99%
“…Intravesical instillation of 1 ml 0.01% DMSO in 0.9% NaCl under 2% isoflurane was used for the vehicle control conditions. Rats remained anesthetized during instillation to suppress the micturition reflex and prevent expulsion of SB505124 (5 M) or 0.01% DMSO (2,3,5). At the conclusion of drug instillation, urinary bladder function tests were repeated and run for at least six reproducible micturition cycles (postdrug).…”
Section: Cystometrymentioning
confidence: 99%